KEMISKINAN, KETIMPANGAN DAN PERTUMBUHAN EKONOMI DI INDONESIA (TINJAUAN ANALISIS REGIONAL) - Wibowo, Tri (Jurnal Kajian Ekonomi dan Keuangan, 2012)
Strategy development pro-growth, pro-job, pro-poor and are listed in the RPJM 2004-2009, have shown encouraging results. During this period of economic growth increased, the unemployment rate declined, so did the level of poverty, but not so with income inequality figures. Menurunannya poverty level has not kept pace with the inequality. Both rural and urban areas, the poverty rate showed a declining trend, but inequality has increased. National development priorities need to pay attention to regions/ provinces that have high levels of poverty and high inequality and low per capita income and slow growth. This area is not a priority when development will potentially social disparities and the potential conflict that would ultimately hamper growth. Indonesia as an agricultural country, the average growth of the agricultural sector has always been below GDP growth, and the growth of a more unstable. Contribution of agriculture to GDP is also declining. The poor are mostly in the agricultural sector, and labor also largely absorbed in agriculture, should receive priority. Agricultural growth will be able to reduce the level of poverty, employment and reducing inequalities, particularly in rural Indonesia.